Perlindungan Hukum terhadap Korban Tindak Pidana Pencurian Data Pribadi - Rosel Denis Pakasi; Yoan B. Runtunuwu; Wenly R. J. Lolong (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to determine the legal protection provided to victims of personal data theft in Indonesia. This study uses a normative juridical research method by examining laws and regulations related to legal protection for victims of personal data theft. The results indicate that legal protection for victims of personal data theft in Indonesia is regulated by Law No. 11 of 2008 concerning Electronic Information and Transactions (ITE) and Law No. 27 of 2022 concerning Personal Data Protection (PDP). However, more effective law enforcement efforts are still needed to protect victims' rights and prosecute perpetrators of personal data theft.